Tula Virus as Causative Agent of Hantavirus Disease in Immunocompetent Person, Germany - Jörg Hofmann (Emerging Infectious Diseases, 2021)
We report molecular evidence of Tula virus infection in an immunocompetent patient from Germany who had typical signs of hantavirus disease. Accumulating evidence indicates that Tula virus infection, although often considered nonpathogenic, represents a threat to human health.